LEVEL PEMBERIAN TEPUNG BIJI KARET TERHADAP PRODUKSI DAN BOBOT TELUR BURUNG PUYUH (Coturnix coturnix Japonica) - Ririn Novita; Betty Herlina; Lepsi Permata (Jurnal Biosilampari : Jurnal Biologi, 2019)
The purpose of this study was to determine how the effect of giving rubber seed flour to the production and weight of quail eggs. Includes ration consumption, egg production, egg weight, and feed conversion, which this research was carried out in this research has been carried out Tanjung Sanai II Village, Kec. Ulak Tanding Padang. This research was experimental and carried out using factorial randomized complete variance analysis (RAL) consisting of 6 treatment levels and 4 replications and each treatment consisted of 4 quails. The treatment used is: P0: 100% Commercial ration without rubber seed flour, P1: 94% Commercial ration + 6% rubber seed flour, P2: 91% Commercial ration + 9% rubber seed flour, P3: 88% Commercial ration + 12% rubber seed flour, P4: 85% Commercial ration + 15% rubber seed flour, P5: 82% Commercial ration + 18% rubber seed flour. The results of this study used the rate of addition of rubber seed flour as much as 18% from the ration given, and significantly affected the conversion of rations and did not significantly affect ration consumption, egg production and egg weight.